Hubungan Konsep Diri dengan Ketangguhan Psikologis pada penderita Diabetes Mellitus - Purba, Anna Wati Dewi; Siregar, Rizky Amalia (MEDIA ILMU KESEHATAN, 2025)
Background: Chronic diseases such. as heart. disease, cancer, stroke, and diabetes mellitus. not only affect physical health but also impose a substantial psychological burden.Objective: This study aimed to analyze the relationship. between self-concept and psychological hardiness among patients with chronic diseases at RSUD Dr. Pirngadi Medan.Methods: A quantitative correlational design was employed with 384 respondents selected through consecutive sampling. The instruments used were a self-concept scale based on Fitts’ theory and a psychological hardiness scale based on Maddi’s theory, both in the form of Guttman scales. Data analysis included validity, reliability, normality, linearity tests, and Pearson Product Moment correlation using SPSS version 25.Results: results showed a very strong and statistically significant positive correlation between self-concept and psychological hardiness (r = 0.814; p < 0.01). The empirical mean score of self-concept was 50.29 compared to the hypothetical mean of 30.50, while the empirical mean score of hardiness was 29.30 compared to the hypothetical mean of 17.00.Conclusion: A positive self-concept contributes to the enhancement of psychological hardiness, supporting therapy success and improving patients’ quality of life. Clinical implications highlight the importance of integrating psychosocial interventions to strengthen self-concept as part of holistic care for chronic disease patients.